Intrasplenic Pancreatic Pseudocyst after Chemoradiation of a Pancreatic Adenocarcinoma Mimicking Progressive Disease: A Case Report and Review of the Literature - Thomas Benter; Oliver Roehr; Lutz Moser; Philipp Kiewe; Leopold Hentschel; Ivan Platzek; Markus K. Schuler (Case Reports in Oncological Medicine)
Chemoradiation is one of the therapeutic options in palliative treatment of locally advanced pancreatic adenocarcinoma, with a well-known safety profile. In this case report, we describe the treatment-related occurrence of an intrasplenic pancreatic pseudocyst which was successfully removed by gastrocystic drainage. This rare complication should be considered in the follow-up and clinical management of patients, particularly if left-sided complaints occur.